Copyright © University of Cambridge. All rights reserved.

## 'Roots and Coefficients' printed from http://nrich.maths.org/

Congratulations Sue Liu of Madras College, St Andrew's on your
solution to this problem. The title of this problem is the clue to
getting a neat solution. We are given:

\begin{eqnarray} \\z_1z_2z_3 &=& 1 \quad
&(1) \\ \\z_1+z_2+z_3 &=& {1\over z_1} + {1\over z_2} +
{1\over z_3} = x \quad &(2).\\ \end{eqnarray}

Just consider the cubic equation $$z^3 + az^2 + bz +c = (z - z_1)(z
- z_2)(z - z_3) = 0$$ with roots $z_1, z_2$ and $z_3$. We know that
$a= -(z_1+z_2+z_3)$, $b= z_1z_2+z_2z_3+z_3z_1$ and $c=
-(z_1z_2z_3)$. As we are given the product of the roots in (1) we
know that $c= -1$.

A little experimentation with the second identity (2) gives a
relationship between $a$ and $b$.

From (2) $${{z_1z_2+z_2z_3+z_3z_1}\over {z_1z_2z_3}} = x$$ and,
using (1) this gives $${z_1z_2 + z_2z_3 + z_3z_1}= x$$ Hence the
cubic equation is $$z^3 - xz^2 + xz - 1 = (z - 1)(z^2 + (1 - x)z +
1) = 0 \quad (3).$$ The factor $(z - 1)$ of this cubic equation
shows that one of the values of z must be 1.

For the other two roots to be real the quadratic factor in (3),
$$z^2 + (1 - x)z + 1 = 0$$ must have real roots in which case

\begin{eqnarray} (1 - x)^2 - 4 &\geq& 0
\\ x^2 - 2x - 3 &\geq& 0 \\ (x + 1)(x - 3) &\geq&
0.\\ \end{eqnarray}

If $(x + 1)(x - 3)\geq 0$ then $x \leq -1$ or $x\geq 3$. So the
other two roots are real when the value of $$ z_1 + z_2 + z_3 =
{1\over z_1} + {1\over z_2} + {1\over z_3}= x $$ is less than or
equal to -1 or greater than or equal to 3.